Loops versus stems: benzylic sulfide oligomers forming carpet type monolayers - Sander, Fabian; Peterle, Torsten; Ballav, Nirmalya; Wrochem, Florian von; Zharnikov, Michael; Mayor, Marcel (The journal of physical chemistry. C, Energy, materials, and catalysis, 2010)
Chainlike oligomers consisting of several meta position interlinked benzylic sulfides and terminal benzylic thiols were synthesized, and the nature of the molecular monolayers formed by their self-assembly on gold (111) substrates was investigated. The fabricated films were characterized by high-resolution X-ray photoelectron spectroscopy and near-edge X-ray absorption fine structure spectroscopy. In the case of the short oligomers, the spectroscopic studies were additionally supported by scanning tunneling microscopy experiments. The target molecules were found to form dense and contamination-free self-assembled monolayer (SAM)-like “carpet” films on gold (111). In spite of the multidentate nature of the benzylic sulfide oligomers, the predominant molecular conformation in these films were bridges (“loops”) formed by the covalent attachment of both terminal thiols with a minor amount of molecules which were bound by only one thiol group as upright standing “stems” protruding the SAM. The films exhibited only a limited degree of order with slight preference of a perpendicular-to-the-surface orientation of the individual phenyl rings of the oligomer chains.
Gesehen am 25.08.2023